2018
DOI: 10.1111/jjns.12208
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular self‐management support program for preventing cardiovascular complication behaviors and clinical outcomes in the elderly with poorly controlled type 2 diabetes mellitus in Indonesia: A pilot study

Abstract: This study revealed that a cardiovascular self-management support program that applies the 5A's self-management support program is feasible for implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 29 publications
(28 reference statements)
1
10
0
1
Order By: Relevance
“…The result of this study was also supported by a study done by Hisni et al (2018), which stated that most patients had type 2 DM for >5 years (66.7%) for macrovascular complications. Factor which significantly associated with complications of peripheral neuropathy, retinopathy, and diabetic foot was a longer duration of diabetes (p<0.001).…”
Section: The Effect Of the Duration Of Illnesssupporting
confidence: 80%
See 1 more Smart Citation
“…The result of this study was also supported by a study done by Hisni et al (2018), which stated that most patients had type 2 DM for >5 years (66.7%) for macrovascular complications. Factor which significantly associated with complications of peripheral neuropathy, retinopathy, and diabetic foot was a longer duration of diabetes (p<0.001).…”
Section: The Effect Of the Duration Of Illnesssupporting
confidence: 80%
“…The average of HbA1c for patients with macrovascular disease was 9.44% (SD= 2.02) compared to 9.18% (SD= 2.04) for those without macrovascular disease (p= 0.11). Hisni et al (2018) on the result of his study showed that after getting self-management support, the experimental group participants showed significant differences in fasting blood sugar, total cholesterol, HDL cholesterol, systolic blood pressure, and diastolic blood pressure before and after receiving the program, on the prevention of cardiovascular complications behavior in older people with uncontrolled type 2 DM. The result of this study was also supported by a study done by Selim (2017) which stated that blood samples of cholesterol, LDL, HDL, trigliserid affected the incidence of type 2 DM complications retinopathy (OR= 1.17; 95% CI= 0.73 to 1.87, diabetic foot ulcers (OR= 2.32, 95% CI= 1.14 to 4.01), and coronary arteries (OR= 1.03; 95% CI= 0.64 to 1.66).…”
Section: The Effect Of Blood Samples On the Macrovascular And Microvascular Complications In Patients Withmentioning
confidence: 99%
“…Studies have shown that persons living with type II diabetes with good self-management practices can reach and sustain glycaemic control and prevent frequent complications, while those that are lax in self-care often develop complications ( Karthik et al., 2020 ; Oluma et al., 2021 ). Self-management support in persons diagnosed with type II diabetes could also improve clinical outcomes, such as fasting plasma glucose, lipid profiles, and blood pressure ( Hisni et al., 2019 ). The leading self-management practices include a healthy diet, physical activity, self-monitoring of blood glucose, adherence to medicine, problem-solving, healthy coping mechanisms, and reducing risk behaviors ( Almutairi et al., 2020 ; Karthik et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dado este escenario, se requieren protocolos más estrictos para tamizar poblaciones en riesgo con el propósito de descartar complicaciones a corto y mediano plazo, además de enfatizar su calidad de prevenibles. En la medida que las estrategias de diagnóstico oportuno se implementen de forma articulada entre los sectores involucrados, el impacto en los distintos niveles de prevención (primario, secundario y terciario) moldeará un perfil epidemiológico con menor carga de estas enfermedades [28][29][30][31] . Estimación de riesgo cardiovascular ateroesclerótico en pacientes adultos F.I.…”
Section: Discussionunclassified